Modeling of bubble column slurry reactor for reductive alkylation of p-phenylenediamine - Chaudhari, Amit S.; Rampure, Mohan R.; Ranade, Vivek V.; Jaganathan, Rengaswamy; Chaudhari, Raghunath V. (Chemical Engineering Science, 2007)
A bubble column slurry reactor (BCSR) model has been developed for the reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) to N, N'-di-secondary-alkyl-p-phenylenediamine (Di-amine). This particular reaction system is commercially relevant and involves a combination of parallel and consecutive reactions comprising equilibrium non-catalytic (homogeneous) and catalytic (heterogeneous) steps. The proposed model is based on the `mixing cell approach'. In this work the mixing cell approach has been extended by including a liquid backflow stream from all but the bottommost mixing cell. The model incorporates the contributions of gas-liquid and liquid-solid mass transfer, heat effects, and complex multistep reaction kinetics. CFD model is used to estimate the extent of backflow among mixing cells and its dependence on operating parameters. The effect of gas and liquid velocities, catalyst loading, inlet PPDA concentration, and temperature on the conversion, selectivity, global rate of hydrogenation, and temperature rise is discussed. The comparison of the current approach with the traditional mixing cell model is discussed. The BCSR model presented here will be useful to provide guidelines for designing and improving overall performance of bubble column reactors. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: bubble columns; CFD; kinetics; Mathematical modeling; Reductive alkylation

Mathematical modeling and simulation of bubble column reactor for aerial liquid phase cyclohexane oxidation - Upkare, Makarand M.; Rajurkar, Kalpendra B.; Gupta, Pankaj R.; Jaganathan, Rengaswamy (International Conference on Modeling, Optimization, and Computing, 2010)
Cyclohexane oxidation is an important but complex commercial reaction, wherein the desired product, K-A oil appears as an intermediates of the reaction sequence. A mathematical model has been developed for the bubble column reactor operating under isothermal conditions. The mass and energy model equations consisted of stiff ODEs. The model was applied to describe the behavior of bubble column reactor for aerial liquid phase cyclohexane oxidation. Effect of initial substrate concentration, catalyst loading and temperature was studied and discussed in detail. Conclusions were presented at the end of the study.
Keywords: K-A Oil Selectivity; Mathematical modeling; substrate conversion and product yield analysis

Two-layer spin coating flow of newtonian liquids: a computational study - Sahoo, Subhadarshinee; Arora, Akash; Doshi, Pankaj (Computers & Fluids, 2016)
Spin coating is the most commonly used method in industries to form coating films of desired thickness and functionality. In case of two-layer spin coating process, stratified layers of two immiscible liquids are deposited onto the substrate simultaneously, which spread and thin to form two-layer coating film of finite thickness. Questions concerning the effect of surface/interfacial tension on uniformity of these films and contact line evolution are relevant and need thorough investigation. Therefore, an axisymmetric model governing the flow of two-layer spin coating process is developed here. Liquids used for the study are assumed to be Newtonian and fully wetting. The contact line singularity is resolved using a precursor layer model and the governing equations are simplified using lubrication approximation. A Galerkin finite-element method (G/FEM) based scheme is developed to solve the resulting fourth order non-linear PDEs. Simulation results reveal that the fluid properties like ratio of the viscosity of upper layer fluid to lower layer and ratio of the upper gas-liquid surface tension to inner liquid-liquid interfacial tension have profound impact on the time evolution of the film profile, contact radius and shape of the capillary ridges. It is observed that a uniform two-layer film surrounded by thin single layer film is formed when the viscosity ratio is small. On the contrary, when viscosity ratio is large, a thin two-layer film surrounded by bulky capillary ridges is formed. Similarly, the results also show that sharpness of capillary ridge increases with decrease in the surface tension ratio. Further, it is found that increase in the precursor layer thickness increases the spreading rate, thereby making the film more uniform. Finally, the uniformity of the final two-layer film does not get affected by the initial volume of fluid present in the upper layer. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Axisymmetric flow; Mathematical modeling; Multi-layer coating; Precursor layer model; Thin-film flow; Two-layer spin coating

Rheological quantification of the extent of dissolution of ultrahigh molecular weight polyethylene in melt-compounded blends with high density polyethylene - Chaudhuri, Krishnaroop; Lele, Ashish K. (Journal of Rheology, 2020)
Melt compounding of ultrahigh molecular weight polyethylene (UHMWPE) with high density polyethylene (HDPE) promises to be an alternative route to prepare bimodal polyethylene grades. However, complete dissolution of UHMWPE in HDPE cannot be guaranteed during melt compounding. Indeed, in an earlier work [K. Chaudhuri et al., Polym. Eng. Sci. 59, 821-829 (2019)], it was shown that a fully entangled UHMWPE did not mix well with commercial HDPE. However, a disentangled UHMWPE (dPE) could be melt-mixed in the same HDPE as evidenced qualitatively by rheological measurements. The present work is focused on quantifying the extent of dissolution of dPE in HDPE. The proposed method involves fitting rheological models for linear viscoelasticity of entangled bimodal blends of polydisperse polymers to dynamic oscillatory shear data and extracting information on the extent of dissolved species. The time-dependent diffusion model of des Cloizeaux is used along with the theory of double reptation (DR) to describe the dynamics of polydisperse homopolymers and also to extract the molecular weight distribution of the UHMWPE sample. A quadratic mixing rule, consistent with the DR model, is used to describe the dynamics of bimodal blends. Melt-mixed dPE/HDPE blends were prepared and characterized for their linear viscoelastic response by frequency sweep tests. The blends showed complex behavior with multiple crossover points, especially for the higher content of dPE. The bimodal model was then fit to the experimental frequency sweep data to determine the only unknown parameter, namely, the extent of dissolved dPE. It was found that a considerable fraction of dPE is dissolved in HDPE during melt compounding.
Keywords: blends; Disentangled UHMWPE; double reptation; HDPE; Mathematical modeling

Mechanistic modeling of continuous capture step purification of biosimilar monoclonal antibody therapeutic - Deulgaonkar, Prashant; Bhambure, Rahul; Prasad, Bhaskarjyoti; Mishra, Ashok; Tiwari, Sanjay; Mody, Rustom (Journal of Chemical Technology and Biotechnology, 2022)
{BACKGROUND Continuous multicolumn Protein A chromatography offers various advantages for capture stage purification of monoclonal antibody therapeutics, like higher productivity and resin capacity utilization, lower buffer consumption, small footprint, etc. Due to the complexity of the continuous process, experimental optimization is time-consuming and cost-intensive. This investigation proposes a hybrid process development approach integrating experimental and mechanistic modeling for time- and cost-effective development and optimization of continuous Protein A affinity chromatography. RESULTS Productivity and capacity utilization of the continuous CaptureSMB process under varying operating conditions were predicted using the Chromatography Analysis and Design Toolkit (CADET) framework and validated with experimental results. Effects of critical process parameters like feed concentration (c(0)), loading breakthrough (s) and residence time (RT) on productivity and capacity utilization were evaluated. Model predictions were validated using the experimental results proving the reliability and feasibility of the modeling approach. At 15.00 +/- 0.20 mg mL(-1) feed model mAb concentration, the model-based approach predicted the best performance giving 27.56 g L-1 h(-1) productivity (RT = 2 min
Keywords: CaptureSMB; continuous chromatography; Mathematical modeling; Protein A; simulation